Exploring Employee Competencies for Organizational Performance: A Comprehensive Analysis - Bett, Davies Kipkorir (Journal of Global Economy, Business and Finance, 2025)
This article delves into the critical topic of employee competencies and their impact on organizational performance. With a focus on human resource capabilities, the study examines the role of competencies in providing sustainable competitive advantages for organizations. By drawing on theories such as the Resource - Based View and the Human Capital theory, the article investigates the relationship between employees knowledge, skills, abilities, and organizational success. The study employs both theoretical and empirical literature reviews to uncover the multifaceted nature of competencies, ranging from analytical thinking and goal setting to self - confidence and problem - solving skills. The research also considers factors influencing employee competencies, including education, training, and experience. Through an analysis of employee knowledge, skills, and experience, the article highlights the vital connection between competencies and organizational effectiveness. The findings underscore the importance of nurturing employee innovation and the need for organizations to adapt and learn from their workforce.